PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING (PjBL)TERHADAP HASIL BELAJAR IPAS SISWA KELAS V SD NEGERI 6 B SRIKATON - Fauziah, Atika; Akmal rijal, Akmal Rijal; Aswarliansyah, Aswarliansyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the level of achievement in IPAS (Natural and Social Sciences) learning outcomes among fifth-grade students at SD Negeri 6 B Srikaton following the implementation of the Project-Based Learning (PjBL) model. A pre-experimental research design was employed. The study population consisted of all 20 fifth-grade students at SD Negeri 6 B Srikaton, and a saturated sampling technique was used. Data collection methods included observation, interviews, tests, and documentation. Data analysis techniques involved calculating the mean, performing a normality test, and conducting a hypothesis test (z-test). The results showed a mean final test score of 81.19. Analysis using the z-z-test at a 5% (0.05) significance level yielded a calculated z-value of 4.09, which exceeds the critical z-value of 1.65; thus, it can be concluded that the implementation of the Project-Based Learning (PjBL) model significantly enabled the fifth-grade students at SD Negeri 6 B Srikaton to meet the Learning Objective Achievement Criteria (KKTP) for IPAS.